The climate bonus: co-benefits of climate policy - Smith, Alison (London, 2013)
"We urgently need to transform to a low carbon society, yet our progress is painfully slow, in part because there is widespread public concern that this will require sacrifice and high costs. But this need not be the case. Many carbon reduction policies provide a range of additional benefits, from reduced air pollution and increased energy security to financial savings and healthier lifestyles, that can offset the costs of climate action. This book maps out the links between low carbon policies and their co-benefits, and shows how low carbon policies can lead to cleaner air and water, conservation of forests, more sustainable agriculture, less waste, safer and more secure energy, cost savings for households and businesses and a stronger and more stable economy. The book discusses the ways in which joined-up policies can help to maximise the synergies and minimise the conflicts between climate policy and other aspects of sustainability. Through rigorous analysis of the facts, the author presents well-reasoned and evidenced recommendations for policy-makers and all those with an interest in making a healthier and happier society. This book shows us how, instead of being paralysed by the threat of climate change, we can use it as a stimulus to escape from our dependence on polluting fossil fuels, and make the transition to a cleaner, safer and more sustainable future."